Acetylcytidine modification of DDX41 and ZNF746 by N-acetyltransferase 10 contributes to chemoresistance of melanoma - Wang, Li; Zeng, Yuefen; Zhang, Ying; Zhu, Yun; Xu, Shuangyan; Liang, Zuohui (Frontiers in Oncology, 2024)
Background: Rapidly developed chemoresistance to dacarbazine (DTIC) is one of thea major obstacles in management of melanoma in the clinical management of melanoma, however, the roles and mechanisms of epi-transcriptomic RNA modification in this process have not been investigated.We established DTIC-resistant (DR) melanoma cells for bulk RNAsequencing, . The expressions of mRNAs waswere detected using qRT-PCR, and protein levels were determined using Western Blotting and Immunohistochemistry. Acetylated RNAs wereas detected by dot blotting and immunoprecipitation sequencing (acRIP-seq). A lung metastasis mouse model of melanoma was established to evaluate the anti-melanoma effects in vivo.Results: We identified that the expression of N-acetyltransferase 10 (NAT10), a catalytic enzyme for the N4-acetylcytidine (ac4C) modification of RNA, was significant upregulated in the DR cells. Clinically, NAT10 expression was elevated in disease progression samples and predicted a poor outcome. Using ac4C RNA immunoprecipitation (ac4c-RIP), we found that the mRNAs of two C2H2 zinc finger transcriptional factors, DDX41and ZNF746, were targets of NAT10-mediated ac4C modification. Gain-and loss-of-function experimentss either in NAT10, or in DDX41 and ZNF746, could altered the chemosensitivity of melanoma accordingly, and the two target genes also negatively correlated with clinical outcomes. Finally, pharmacological inhibition of NAT10 with Remodelin sensitized melanoma cells to DTIC treatment in vitro and in a mouse xenograft model.Our study elucidates the previously unrecognized role of NAT10-mediated ac4c-modification in the chemoresistance of melanoma, and provides a rationale for developing new strategies to overcome chemoresistance inof melanoma patients.